STUDY OF PHENOMENOLOGY-HERMENITIC ON SUNDANESE VERNACULAR ARCHITECTURE PUBLIC SPACE - NURYANTO, NURYANTO NURYANTO (Journal of Architectural Research and Education, 2020)
This research is motivated by the phenomenon of inter-building space which is understood as an open area and can be accessed by people who are usually located between buildings. This study is a case study on public spaces in kampung Kasepuhan Ciptarasa and Ciptagelar, Sukabumi-West Java. The space between buildings in this study is interesting because in it public activities and rituals on a community scale can be held which are quite limited. The community itself becomes the agent responsible for care. The purpose and significance of public space research lie in the disclosure of open space phenomena that are local and participatory. The research method used is phenomenology-hermeneutics to find out the meaning of interpretation of the text of a phenomenon of public space that occurs. The results showed that the use of public space for the residents of kampung Kasepuhan Ciptarasa and Ciptagelar due to ritual activities, especially Seren Taun. Beyond that, the function of public space is not visible. This reflects the position of the importance of the presence of public space only to facilitate the activities of the rite of the community.Â Keywordâ€”phenomenology-hermeneutic, text, public space, ritual, vernacular